Work, family and commuting in Europe : the lives of Euro-commuters - Ralph, David (Palgrave pivot, 2014)
Since the onset of the economic crisis, the migration of European citizens within the European Union -- intra-European migration -- has increased dramatically. Severe recession in some older Western EU countries has led to a sharp rise in labour migration of young Europeans from these countries to other EU states. But amid these shifting migration patterns, another group of migrants has emerged. A growing number of European citizens now work in one EU country, but live in another, shuttling between the two on a routine basis. Work, Family and Commuting in Europe examines this ever-expanding group of 'Euro-commuters'. It examines their lives betwixt-and-between two EU countries, and addresses the following questions: Who are these Euro-commuters? What are their motives for undertaking this particular form of migration? How does commuting across the EU influence their personal, family, and social lives? And, what is the future for this unorthodox type of European migration?